Reaching a consensus in multi-agent systems: a nonlinear protocol - Saburov, Mansoor; Yusof, Nur Atikah (2014)
Multi-Agent Systems (MAS) give a complete description for large-scale systems consisting of small subunits, called agents. The behavior of MAS is particularly interesting because the agents may fulfill certain tasks as a group, even in the individual agent does not know about the overall task. MAS have attracted more and more interest in recent years. A lot of examples come from nature, such as schooling fishes or fireflies flashing in unison. A collective behavior is also interesting for engineers when solving problems such as flocking or synchronization. This is mainly due to its important applications, including the cooperative control of unmanned air vehicles (UAVs), autonomous underwater vehicles, congestion control in communication networks, swarms of autonomous vehicles or robots, autonomous formation fight, etc. In all cases the goal is to control a group of agents connected through a communication network to reach an agreement on certain quantities of interest. This problem is called the consensus problem. Most researches in the study of discrete-time MAS, presented in the past few years, have considered linear cooperative rules. However, local interactions between agents are more likely to be governed by nonlinear rules. In this poster, we investigate the consensus of discrete-time MAS with time invariant/varying nonlinear cooperative rules. Based on our presented nonlinear model, we show a consensus in the discrete-time MAS. Our model generalizes a classical time invariant DeGroot model. It seems that, unlike a linear case, a consensus can be easily achieved a nonlinear case.